Towards a Theory and Policy of Eco-Innovation - Neoclassical and (Co-)Evolutionary Perspectives - Klaus Rennings (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1998)
Innovation processes toward sustainable development (eco-innovations) have received increasing attention during the past years. Since existing theoretical and methodological frameworks do not address these problems adequately, research need can be identified to improve our understanding of innovation processes toward sustainability in their different dimensions, complex feedback mechanisms and interrelations. This paper discusses the potential contribution of neoclassical and (co-)evolutionary approaches from environmental and innovation economics to fill this gap. It is argued that both approaches have their merits and limits concerning a theory and policy of ecoinnovation. Neoclassical methods are most elaborated to analyze the efficiency of incentive systems which seems to be essential for stimulating innovation. Evolutionary approaches are more appropriate for analyzing long-term technological regime shifts. On this theoretical basis, a crucial question is if innovations toward sustainability can be treated like normal innovations or if a specific theory and policy are needed. Three specialties of eco-innovation are identified: the double externality problem, the regulatory push/pull effect and the increasing importance of social and institutional innovation. While the first two of them are widely ignored in innovation economics, the third is at least not elaborated appropriately. The consideration of these specialties may help to overcome market failure by establishing a specific eco-innovation policy and to avoid a "technology bias" by a broader understanding of innovation. Eco-innovation policy requires close coordination with environmental policy in all innovation phases. Environmental and eco-innovation policy can be regarded as complementarily. However, an environmental policy neglecting the potentially beneficial effects of a specific eco-innovation policy (especially in the invention phase) may lead to excessive economic costs. Due to the specialties of eco-innovation, it seems moreover to be crucial to strengthen the importance of social and institutional innovation in both eco-innovation theory and policy.
Keywords: 330; eco-innovation; innovation theory; co-evolution; double externality; regulatory push/pull effect; social innovation; institutional innovation; Umwelttechnik; Innovation; Umweltökonomik; Evolutionsökonomik; Umweltpolitik; Innovationspolitik; Theorie